The last odyssey [compact disc, unabridged] - Rollins, James, 1961- (Rollins, James, 1961- Sigma Force novel., 2020)
In the frozen tundra of Greenland, a group of modern-day climatologists and archaeologists stumble on a medieval ship buried a half-mile below the ice. Inside the captain's cabin is a magnificent treasure: a clockwork gold atlas encircled by an intricate silver astrolabe. The mechanism is signed with the name of its creator, Ismail al-Jazari, a famous Muslim inventor considered to be the Da Vinci of the Arab world. Once activated, the moving globe traces the path of Odysseus' famous ship as it sailed away from Troy. But the route detours as the map opens to reveal a hidden realm underneath the Mediterranean Sea. The map indicates that this subterranean world is called Tartarus, the Greek name for Hell. When word of Tartarus spreads, tensions explode in this volatile region where terrorists wage war and civilians suffer untold horrors. Now, Sigma Force must go where humans fear to tread. To prevent a tyrant from igniting a global war, they must cross the very gates of Hell.